Financial Feasibility and Sensitivity of Gouramy Culture (Osphronemus Gouramy) Business at Susuhbango Village, Kediri Regency - Mochammad Fattah; Tiwi Nurjannati Utami; Dwi Sofiati (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2019)
This research aimed to analyze the feasibility and to analyze the sensitivity of the gouramy culture. Quantitative research methods used in this study with the total number of respondents were 43 farmers. The feasibility analysis of financial using NPV, B/C, IRR, and PP.  The sensitivity analysis using the assumption of rising costs, decreasing costs as well as the acceptance and receipt changes simultaneously. The results showed that the value of NPV was IDR 14.083.504, B/C were 3.07, IRR was 54% and PP was 1.84 years. So that it can be said that the gouramy culture was infeasible condition. The gouramy culture conditions were sensitive to the cost increases to 30%. The decline of revenue caused the business in unfeasible condition until 21%. Whereas, the combination of these two conditions within costs increase to 16% and a decrease to 10% caused the business in unfeasible condition.